Apocalyptic time - Baumgarten, Albert I. (Studies in the history of religions, 2000)
The theme of this volume is the nature and perception of time in millennial movements. The authors adopt a number of disciplinary approaches to the topic, analyzing millennial movements from the three Abrahamic faiths, as well as from the East